Clinical research with probiotics as an indicator of global valorization since the year 2000 - Wiegers, Cato; van Beek, Eveline H. T.; Larsen, Olaf F. A. (Frontiers in Microbiology, 2023)
Probiotics are becoming increasingly popular due to their potential health benefits. With this rise in popularity and demand as indicated by ever-growing market prospects, it seems evident that innovation and valorization are on the rise as well. However, an increasing body of literature shows that innovation is stagnating, which may be detrimental to the exploitation of the benefits of probiotics, for example the development of alternative therapies to manage the increasing prevalence of metabolic and autoimmune disorders. To this end, this study investigated global clinical trials that have been executed since the year 2000 as a first indicator of the status of probiotic valorization. The cumulative number of clinical trials has indeed increased significantly from 0 at the start of the century up to 2,517 registered trials in 2023. However, in Asia, Europe, and North America, the continents with the highest numbers of clinical trials, stagnating or declining trends have been found. In these locations, most clinical trials were funded by non-industry sponsors and targeting probiotic supplements or undefined products. Considering the overall stagnation in clinical trials and viewing these trends in the context of developments in local markets and regulations, the global valorization of probiotics appears to slow down. This could impact the transition from academic research to the development of products that are beneficial and accessible for consumers, either to maintain a healthy lifestyle or to treat medical conditions.